2020
DOI: 10.3390/su12229495
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Environmental Issues by African Americans/Blacks in Washington, DC, USA: Giving Voice to the Voiceless

Abstract: Our study elucidated knowledge and perceptions of natural resources and climate change by African Americans/Blacks in Washington, DC since they are a traditionally marginalized population and to see if we could dispel the perception that they have low knowledge and interest in environmental issues. Secondarily, we wanted to determine if knowledge and perceptions vary across age groups. We conducted a survey of 491 Blacks in the District and asked 26 questions/statements related to natural resources, climate ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Previous studies have focused on macro-and mesoscopic analyses of public environmental awareness, including the construction of indicator systems [6] and surveys of environmental awareness among specific groups [7]. Additionally, the source [8] and presentation [9] of information services can affect the impacts of information, and the existing cognition or capability [10] and value preferences [11] of the public can affect their understanding of information. It has been demonstrated that information service quality is an important predisposing factor for public environmental awareness, but this neglects the influences of intermediate variables on public environmental awareness and pays insufficient attention to the influencing mechanism of psychology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on macro-and mesoscopic analyses of public environmental awareness, including the construction of indicator systems [6] and surveys of environmental awareness among specific groups [7]. Additionally, the source [8] and presentation [9] of information services can affect the impacts of information, and the existing cognition or capability [10] and value preferences [11] of the public can affect their understanding of information. It has been demonstrated that information service quality is an important predisposing factor for public environmental awareness, but this neglects the influences of intermediate variables on public environmental awareness and pays insufficient attention to the influencing mechanism of psychology.…”
Section: Introductionmentioning
confidence: 99%